Evaluation of Horn Bud Wound Healing Following Cautery Disbudding of Dairy Calves With and Without the Use of Oxytetracycline Aerosol Spray - Ridgway, Rachel; Neary, Joseph; Turner, Andrea; Barrett, David C.; Gillespie, Amy (Frontiers in Veterinary Science, 2022)
Oxytetracycline is commonly applied as a topical agent to burn lesions post cautery disbudding of calves. Judicial use of antibiotics dictates that they should only be used were necessary to reduce the development of resistance in target bacteria. The objective of this study, therefore, was to assess the efficacy of topical oxytetracycline spray on wound healing post cautery disbudding of dairy calves and evaluate wound healing over a six-week period. Dairy calves were disbudded by veterinarians, technicians, or veterinary students, using a standard cautery disbudding protocol. Oxytetracycline was randomly applied to the right or left horn bud of each animal (OXY) and the other horn bud received no antibiotic spray (NA). The outcomes measured were wound diameter (WD) and lesion score (LS), either normal healing (NH) or abnormal healing (AH). These assessments were conducted every 14 days following disbudding. A total of 360 animals completed the study. There was a difference in wound diameter and lesion score on day 14 post disbudding between the two groups. Cautery lesions sprayed with oxytetracycline (OXY) were 0.5 ± 0.15 mm smaller than NA lesions (P=0.001) and there were fewer abnormal healing lesions for OXY compared to the NA (2.5% vs 11%, respectively; P=<0.001). There were no differences at day 28 and day 42 post disbudding and on day 42 both groups had 34% of wounds healed. In summary, oxytetracycline spray improved wound healing at 14 days post disbudding relative to no topical antibiotic, however, not in the longer term.